Research on Shaking Force and Shaking Moment Balancing or Spatial Linkage - Zhao Xinhua (Jixie chuandong)
In this paper; using the method of dynamic Mass -replace, in the dynamic balance of spatial mechanisms, the mass distribution matrix that has to be satisfied for the spatial Component is first obtained through an example of spherical four-bar linkage and the shaking force and the shaking moment of this spherical four-bar linkage is balanced then.